Fotogrametrični poligon za zajem podatkov v zaprtih prostorih - Kozmus Trajkovski, Klemen (Geodetski vestnik, 2025)
The article presents the use of photogrammetric traverses for image orientation and the acquisition of mass spatial data in environments where GNSS (Global Navigation Satellite Systems) or tachymetric surveys are not available or not reliable, such as inside buildings. The photogrammetric traverses were tested indoors. The basic idea of a photogrammetric traverse is to start from an area where the positions of the ground control points are surveyed and then use a still camera to develop a traverse of overlapping images. The images are then processed with SfM (Structure from Motion) to calculate their orientation and accuracy of points along the traverse. The study tested the accuracy and reliability of linked, looped and open photogrammetric traverses. The positional accuracy of the check points was better than 10 cm, even when adjusting several hundred images in the least accurate open traverse.
Keywords: določanje položaja; fotogrametrija; grajenje strukture iz gibanja; izmera; masovni zajem prostorskih podatkov; mass spatial data acquisition; photogrammetry; poligon; positioning; Structure from Motion; survey; traverse